Association between urinary arsenic species and vitamin D deficiency: a cross-sectional study in Chinese pregnant women - Zhang, Jingran; Bai, Yuxuan; Chen, Xi; Li, Shuying; Meng, Xiangmin; Jia, Aifeng; Yang, Xueli; Huang, Fenglei; Zhang, Xumei; Zhang, Qiang (Frontiers in Public Health, 2024)
Background: An increasing body number of studies suggest that environmental pollution can elevate the risk of vitamin D deficiency (VDD). However, there was less knowledge regarding arsenic (As) exposure and VDD, particularly in Chinese pregnant women.: This study examines the correlations of different urinary As species with serum 25(OH)D and evaluates VDD prevalence. Method: We measured 391 pregnant women's urinary arsenite (As 3+ ), arsenate (As 5+ ), monomethylarsonic acid (MMA), and dimethylarsinic acid (DMA) levels and serum 25(OH)D2, 25(OH)D3, 25(OH)D levels in Tianjin, China. The diagnosis of VDD was based on serum levels of 25(OH)D. Generalized linear models (GLMs) Linear relationship, Logistics regression, and Bayesian kernel machine regression (BKMR)were used to examine the associations between urinary As species and VDD.Results: Among the 391 pregnant women, 60 received a diagnosis of VDD. Baseline information showed significant differences in As 3+ , DMA, and tAs distribution between pregnant women with and without VDD. The Logistics regression showed that As 3+ was significantly and positively correlated with VDD (OR: 4.65, 95% CI: 1.79, 13.32).Meanwhile, there was a marginally significant positive correlation between tAs and VDD (OR: 4.27, 95% CI: 1.01, 19.59). The BKMR revealed positive correlations between As 3+ , MMA and VDD. However, negative correlations were found between As 5+ , DMA and VDD.Conclusions: According to our study, there were positive correlations between iAs, especially As 3+ , MMA and VDD, but negative correlations between other As species and VDD. Further studies are needed to determine the mechanisms that between different As species and VDD.